Towards a Stronger Voice for Polish Science: 20th World Economic History Congress, Lund, 28 July – 1 August 2025 - Bębnowski, Damian (Studia Historiae Oeconomicae, 2025)
The report concerns the XX World Economic History Congress (WEHC), organized by the International Economic History Association (IEHA), which took place in Lund from July 28 to August 1, 2025, on the theme “Equality & Sustainability Challenges.” The event was attended by approximately 1,140 researchers from 58 countries, representing various disciplines and theoretical and methodological approaches to economic history. The congress included approximately 250 sessions, competitions, discussion panels, a publishing exhibition, and integration events. Particularly noteworthy is the growing activity of Polish scholars – 26 researchers from Poland and 6 from the Polish diaspora participated in Lund, which is a record representation compared to previous editions. Poles co-organized several sessions on economic transition in Central and Eastern Europe, socio-economic inequalities, and the economic history of empires in Eastern Europe. One of these was organized for the first time by the Polish Association of Economic History. The papers were in line with the main themes of the congress, although the issues of the Central and Eastern European region were treated marginally. The author emphasizes the importance of a stronger voice for Polish economic historiography in the global scientific debate.